Enhanced Antilipopolysaccharide (Lps) Induced Changes in Macrophage Functions by Rubia Cordifolia (Rc) Embedded with Au Nanoparticles - Singh, D (2013)
In this paper, we have shown that gold nanoparticles (Au (NPs)) embedded in Rubia cordifolia (RC) matrix (RC-Au (NPs)) exhibit a high therapeutic value relating to its anti-inflammatory characteristics. It was prepared by utilizing the reducing properties of RC to convert HAuCl4 into Au (NPs). In order to compare its effectiveness, with respect to Au (NPs), the latter was synthesized separately by reducing HAuCl4 with lemon extract. These Au (NPs) along with RC-Au (NPs) were characterized by X-ray diffractometry (XRD), transmission electron microscopy (TEM), and UV-visible spectroscopy. The enhancement in anti-inflammatory characteristics was assessed as its inhibitory potential for lipopolysaccharide (LPS)-induced nitric oxide (NO) release, by rat peritoneal macrophages. The RC-Au (NPs) significantly enhanced its potential to inhibit NO release, which was reported in terms of inhibitory concentration for 50% inhibition (IC50=11.98 ng/ml), as compared to either RC extract (IC50=47 × 103 ng/ml) or to Au (NPs) (IC 50=587.50 ng/ml). © 2013 Elsevier Inc.